2003
DOI: 10.1097/00002030-200307250-00013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the HIV epidemic in sub-Saharan Africa on the pattern of HIV in the UK

Abstract: Infections acquired in Africa and among Africans are making an increasing contribution to HIV infection in the United Kingdom. Migration, diagnosis of long-standing infection and incident cases are all potential influences, but they are difficult to measure. Improvement in early diagnosis of HIV continues to be an important component of intervention to prevent onward vertical and sexual transmission and to promote access to treatment and care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 6 publications
1
33
0
1
Order By: Relevance
“…Similar to trends seen in other developed countries [22][23][24][25][26][27][28][29], our immigrant/refugee population, especially those from Sub-Saharan Africa, is diagnosed at a later stage in their HIV infection, with lower CD4 counts, a larger percentage of females, different HIV subtypes, and a different array of co-morbidities previously rare for Canada, such as tuberculosis and toxoplasmosis. We found that management and monitoring of disease progression is more intense, requiring more clinic al visits and laboratory testing to anticipate the different responses to treatment by the various non-B subtypes as discussed in Spira et al [18].…”
Section: Discussionsupporting
confidence: 77%
“…Similar to trends seen in other developed countries [22][23][24][25][26][27][28][29], our immigrant/refugee population, especially those from Sub-Saharan Africa, is diagnosed at a later stage in their HIV infection, with lower CD4 counts, a larger percentage of females, different HIV subtypes, and a different array of co-morbidities previously rare for Canada, such as tuberculosis and toxoplasmosis. We found that management and monitoring of disease progression is more intense, requiring more clinic al visits and laboratory testing to anticipate the different responses to treatment by the various non-B subtypes as discussed in Spira et al [18].…”
Section: Discussionsupporting
confidence: 77%
“…These findings are consistent with the geographic distribution of the countries of origin of the African-born population surveyed, with over 50% being from East Africa (primarily Somalia and Ethiopia) and 30% from various West African countries (including Liberia, Cameroon, Cote d'Ivoire, and Sierra Leone). As yet there is no evidence to suggest that transmission of non-B subtype viruses has expanded beyond the African-born population of Minnesota, a phenomenon described in other parts of the world where similar demographic shifts to those seen here have occurred [Parry et al, 2001;Sinka et al, 2003]. The possibility of such an expansion of non-B HIV-1 viruses has resulted in the development of a program by the Minnesota Department of Health for conducting ongoing active surveillance of viral diversity in newly diagnosed HIV-1 infected Minnesotans that is scheduled to commence in the summer of 2005.…”
mentioning
confidence: 66%
“…An unlinked and anonymous seroprevalence survey undertaken among heterosexual attendees at seven genitourinary medicine clinics in London between 1999 and 2000 found that 1 in 16 women and 1 in 33 men born in sub-Saharan Africa were infected with HIV. In addition, 39% of those that were HIV positive remained undiagnosed after the visit (Sinka, Mortimer, Evans, & Morgan, 2003). Mayisha II, a UK study involving over 1000 African men and women, found that two-thirds of its HIV positive respondents were undiagnosed (Mayisha II, 2005).…”
Section: Hiv Diagnosis and Late Presentationmentioning
confidence: 99%